Laboratory modeling of siphon drainage combined with surcharge loading consolidation for soft ground treatment. Issue 8 (17th November 2018) - Sun, Hongyue; Wu, Gang; Liang, Xu; Yan, Xin; Wang, Dongfei; Wei, Zhenlei
ABSTRACT: Conventional drainage consolidation methods cause significant energy consumption and environmental issues. In this paper, a method combining siphon drainage and surcharge loading is proposed to drain water from soft soil with vertically installed prefabricated vertical drains (PVDs) and a siphon tube. To investigate the availability and effectiveness of this method, a laboratory physical modeling test was conducted to investigate the drainage and consolidation behavior. The laboratory modeling test results of this method were compared with the calculated results of the ideal sand-drained ground consolidation method to clarify the advantages and mechanism of this method. Comparison results show that the pore pressure and settlement in the proposed method developed faster than the calculation results of ideal sand-drained consolidation theory. About 10 m thickness of unsaturated zone can be formed by siphon drainage which produce a surcharge loading effect on the soil below the flow profile. Drainage is a very slow process in soft soil, and siphon drainage can work continually. Siphon drainage combined with surcharge loading is potentially a good alternative to drain water from soft clay economically and environmentally.